Surface Enhanced Raman Correlation Spectroscopy of Particles in Solution - Asiala, Steven M. (American Chemical Society, 2014)
[Image: see text] Surface enhanced Raman correlation spectroscopy (SERCS) is shown as a label-free, chemically specific method for monitoring individual polymer beads and lipid vesicles interacting with a 2-D planar surface enhanced Raman (SERS) substrate in solution. The enhancement afforded by the SERS substrate allows for spectral data to be acquired in series at rates between 31 and 83 Hz. Auto- and cross-correlation of spectral data facilitates the measurement of diffusion constants for particles ranging in radius from 50 to 500 nm while discriminating signal associated with the target analyte from extraneous fluctuations. The measured diffusion coefficients are on the order of 10(–10)–10(–11) cm(2)/s, a factor of 40 times slower than predicted from the Stokes–Einstein equation, suggesting that particles are experiencing hindered diffusion at the surface. The enhanced signals appear to originate from particles less than 5 nm of the SERS substrate, consistent with adsorption to the surface. This work provides a means to measure and monitor surface interactions and demonstrates the utility and limits of SERS detection in solution over planar SERS substrates.